Role of rural girls of development of extension work in Iraq (Article review) - Hafsa Hade; Abdalaziz Midhas (مجلة جامعة كركوك للعلوم الزراعية, 2022)
In conclusion, young rural women have a major role in agricultural production anddomestic work, and this reflects their positive role in agricultural extension work with rural men andwomen, especially young rural women, and through field visits to researchers in this field, andasking some questions by researchers to rural women and farmers on some farms, In which youngwomen work, about the role of young women’s participation in agricultural work and the home, andthe answer was that they work the most in the field of agriculture and household belongings,thus therural youth is considered the strong support for her father, brother and mother in the field and thehouse, and the percentage of their work relative to all the workers of her family members in thefield and the house is large, as the percentage of her work in the field was about (45%) and thepercentage of her work in the house is about (55%). The percentage is large in relation to the workof the remaining members of their families.